Monitoring model drug microencapsulation in PLGA scaffolds using X-ray powder d - Adeyinka Aina; Manish Gupta; Yamina Boukari; Andrew Morris; Nashiru Billa; Stephen Doughty (Elsevier, 2016)
The microencapsulation of three model drugs; metronidazole, paracetamol and sulphapyridine into Poly (dl-Lactide-Co-Glycolide) (PLGA) scaffolds were probed using X-ray Powder Diffraction (XRPD). Changes in the diffraction patterns of the PLGA scaffolds after encapsulation was suggestive of a chemical interaction between the pure drugs and the scaffolds and not a physical intermixture.